An electrochemical study based on thymine–Hg–thymine DNA base pair mediated charge transfer processes1. Issue 61 (4th July 2015) - Xu, Ensheng; Lv, Yanqin; Liu, Jifeng; Gu, Xiaohong; Zhang, Shuqiu
<x xml:space="preserve">Abstract</x> The (TT)n might have more π-overlapping than the corresponding matched base pairs, and the intercalation of Hg(ii) into TT may further increase this overlapping, causing faster CT kinetics.